Waqf reporting and governance of Johor and Federal Territory Islamic Religious Councils / Dalila Daud - Daud, Dalila (2017)
Waqf plays a critical role within the Islamic society. Indeed, it is a central feature in Islamic religious practices, socio-economy activities, poverty alleviation programs, charity, health, education as well as ways in curbing social problems. Despite its importance, there is a notable lack of proper waqf reporting among the Islamic Religious Councils who are responsible in waqf administration and control. As far as the waqf councils are concerned, there are serious questions regarding the quality and level of reporting conducted, which, in turn, reflects the ineffectiveness of the councils' governance. Even though it is clear that the councils' situation is dire, there have been few studies carried out to investigate this concern. The thesis therefore addresses this literature gap by providing insights on waqf reporting and governance of Islamic Religious Councils. Iff particular, this study aims to investigate the current practice and the governance practice in Islamic councils. These research issues are examined using a qualitative research methodology involving two Islamic councils in Malaysia. Drawing from the literature, a proposed framework of Eisenhardt (1989) is used to interpret the case evidence. The results show that a lack of transparency is the most serious problem faced by the councils. This problem is derived from several attributes consisting of bureaucracy, policies, conflict of interest and limited support from authority. The results of this study provide additional insights into how waqf governance among Islamic Councils in Malaysia can be improved. Thus, this research provides an opportunity for the wa^/practitioners to gain a better understanding of how governance could be leveraged to enhance the councils' performance in reporting. For academicians, insights from this study will add to the body of knowledge particularly on the integration of the accountability theory and the stakeholder theory to examine whether the council is performing and fulfilling the intention of interested parties, whilst introducing the "triple accountability" in order to meet the demand of reporting to stakeholders.